Golf ball and method of manufacturing same

A two-layer coating system with specific resin compositions and solvent properties addresses the peeling and adhesion issues of high elastic recovery coatings on golf balls, enhancing scratch resistance and aerodynamic performance.

JP7608149B2Active Publication Date: 2025-01-06BRIDGESTONE SPORTS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020213452
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-23
Publication Date
2025-01-06
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing golf ball coatings with high elastic recovery rates for scratch resistance tend to peel easily from the cover, especially on dimples, leading to reduced aerodynamic performance due to uneven film thickness and poor adhesion.

Method used

A two-layer coating system is applied, with a first coating composed of an acrylic resin and urethane resin for improved adhesion, followed by a second polyurethane coating with a solvent boiling point of 80°C or less, ensuring a minimum thickness of 10 μm at the dimple edges and an elastic recovery rate of 50% or more.

Benefits of technology

The method ensures uniform coating thickness and enhanced scratch and peeling resistance, maintaining the golf ball's aerodynamic performance by improving adhesion and film uniformity on dimples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608149000002
    Figure 0007608149000002
  • Figure 0007608149000001
    Figure 0007608149000001
Patent Text Reader

Abstract

To provide a golf ball capable of evenly forming a thick coating film on a dimple surface including an edge part, and excellent in both scratch resistance and peel resistance, and to provide a manufacturing method of the same.SOLUTION: A manufacturing method of a golf ball includes forming a first coating film on a surface of a cover having a plurality of dimples, and forming a second coating film on a surface of the first coating film. The second coating film is made from a second coating composition containing polyurethane coating and a solvent having a boiling point of 80°C or less. The second coating film has an elastic recovery rate of 50% or more. In the golf ball thus obtained, an edge ratio as a ratio of a film thickness of the second coating film in the edge part of the dimple to a film thickness of the second coating film in the central part of the dimple is 50% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a golf ball and a method for manufacturing the same. [Background technology]

[0002] For the purpose of protecting the surface of a golf ball and maintaining a good aesthetic appearance, the surface of the golf ball is usually coated with a paint composition. When the surface of a golf ball is scratched, even if the scratch is small, dirt, grass, etc. can get into the scratch and cause contamination of the surface of the golf ball.

[0003] Therefore, in order to form a coating film with high scratch resistance on the surface of a golf ball, a coating composition capable of forming a coating film with a high elastic work recovery rate has been proposed. For example, JP 2017-077357 A describes a golf ball coating composition whose main component is a urethane coating made from a polyol and a polyisocyanate, in which an acrylic polyol is used as the polyol and the coating film formed from the composition has an elastic work recovery rate of 70% or more. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2017-077357 Summary of the Invention [Problem to be solved by the invention]

[0005] Although the coating film with high elastic recovery rate produced by the above-mentioned coating composition has high scratch resistance, it has had a problem in adhesion to the cover of the golf ball. Compared with ordinary coating films, the material of the coating film with high elastic recovery rate is brittle, and it tends to peel off easily from the cover or from the mark printed on the cover, especially when the cover is hard.

[0006] After extensive research into achieving both scratch resistance and adhesion (peel resistance), it was discovered that increasing the thickness of the coating film could improve both scratch resistance and peel resistance, but it was also found that it was difficult to form a thick, uniform coating film with the above-mentioned coating composition with high elastic recovery, particularly on surfaces with concave curves such as dimples. In particular, the coating film thickness was thin at the edges of the dimples, where they adjoined the rest of the ball surface (bank portions), which meant that scratch resistance and peel resistance could not be sufficiently improved, and this could also lead to a deterioration in the aerodynamic performance of the golf ball.

[0007] In view of the above problems, the present invention aims to provide a golf ball that can form a thick, uniform coating on the dimple surface, including the edge portions, and that has excellent properties in both scratch resistance and peel resistance, and a method for manufacturing the same. [Means for solving the problem]

[0008] In order to achieve the above-mentioned object, one aspect of the present invention is a method for manufacturing a golf ball, which includes the steps of forming a first coating film on the surface of a cover having a plurality of dimples, and forming a second coating film on the surface of the first coating film, wherein the second coating film is formed from a second coating composition containing a polyurethane paint and a solvent having a boiling point of 80°C or less, and the second coating film has an elastic recovery rate of 50% or more.

[0009] The thickness of the second coating film at the edge portions of the dimples is preferably 10 μm or more.

[0010] The first coating film is preferably formed from a first coating composition containing an acrylic resin and a urethane resin, and the ratio of the acrylic resin to the total mass of the acrylic resin and the urethane resin is preferably 50 mass % or more.

[0011] The second coating film is preferably formed by spray coating.

[0012] The blending amount of the solvent having a boiling point of 80° C. or less relative to the total amount of the second coating composition is preferably 20 mass % or more.

[0013] In another aspect, the present invention provides a golf ball comprising a core, a cover having a plurality of dimples, and a coating film located on the surface of the cover, wherein the coating film has a laminated structure including at least a first coating film on the inside of the golf ball and a second coating film on the outside of the golf ball, the second coating film comprising polyurethane paint, the second coating film having an elastic recovery rate of 50% or more, and an edge ratio, which is the ratio of the thickness of the second coating film at the edge of the dimple to the thickness of the second coating film at the center of the dimple, of 50% or more.

[0014] The thickness of the second coating film at the edge portions of the dimples is preferably 10 μm or more.

[0015] The first coating film is preferably formed from a first coating composition containing an acrylic resin and a urethane resin, and the ratio of the acrylic resin to the total mass of the acrylic resin and the urethane resin is preferably 50 mass % or more. [Effects of the Invention]

[0016] According to the present invention, a first coating film and a second coating film containing a polyurethane paint with an elastic recovery rate of 50% or more are sequentially formed on the surface of a cover having a plurality of dimples, the coating film having a laminate structure of at least two layers consisting of an inner coating film and an outer coating film, and a solvent with a boiling point of 80°C or less is blended into the second coating composition that forms the second coating film (outer coating film).This results in an edge ratio of 50% or more, which is the ratio of the thickness of the outer coating film at the edge of the dimple to the thickness of the outer coating film at the center of the dimple.This allows a thick coating film to be formed uniformly on the dimple surface, including the edge portions, thereby providing a golf ball with excellent properties in both scratch resistance and peel resistance. [Brief explanation of the drawings]

[0017] [Figure 1] 1 is a cross-sectional view schematically showing the periphery of a dimple of a golf ball according to the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0018] An embodiment of a golf ball and a method for manufacturing the same according to the present invention will now be described.

[0019] The method for manufacturing a golf ball of this embodiment includes the steps of forming a first coating (also called an "inner coating") on the surface of a cover having a plurality of dimples, and forming a second coating (also called an "outer coating") on the surface of the first coating.

[0020] The first coating composition for forming the inner coating film is preferably, but not limited to, one containing an acrylic resin and a urethane resin as the main components. Since the cover of a golf ball contains an ionomer resin, a urethane resin, or the like as the main component, by using an acrylic resin and a urethane resin in the inner coating film that contacts both the cover and the outer coating film, it is possible to increase the affinity with the cover and the adhesion with the outer coating film.

[0021] The ratio of acrylic resin to urethane resin (acrylic resin:urethane resin) is preferably 30:70 to 80:20 by mass, more preferably 50:50 to 80:20, and even more preferably 60:40 to 70:30. In particular, increasing the acrylic resin ratio can improve adhesion to the ionomer resin contained in the cover, so the acrylic resin ratio is preferably 50% by mass or more. On the other hand, increasing the urethane resin ratio can improve the abrasion resistance of the entire coating film (a laminate of the inner and outer coating films) because of the flexibility of the urethane resin.

[0022] Examples of acrylic resins include resins obtained by polymerizing one or more acrylic monomers selected from the group consisting of acrylic acid, methacrylic acid, and their esters, and resins obtained by copolymerizing one or more acrylic monomers with one or more monomers other than acrylic monomers. Specific examples of acrylic esters and methacrylic esters among acrylic monomers include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and glycidyl (meth)acrylate. Specific examples of monomers other than acrylic monomers include styrene. Of these, acrylic esters are preferably used as acrylic resins to improve adhesion.

[0023] The urethane resin may be, for example, a resin having a urethane bond obtained by reacting a polyol component with a polyisocyanate component. Examples of the polyol component include polyester, polyether, and polycarbonate. Examples of the polyisocyanate component include tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (hydrogenated MDI), naphthalene-1,5-diisocyanate (NDI), xylylene diisocyanate (XDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI). Of these, it is preferable to use a polyether type urethane resin to impart flexibility.

[0024] The first coating composition is preferably an aqueous coating composition. An aqueous coating composition is one in which a resin, which is the main component, is dissolved or dispersed in water. Aqueous coating compositions are classified into water-soluble coating compositions and water-dispersible coating compositions depending on the stability state of the resin in water. In this embodiment, a water-dispersible coating composition is preferred. Water-dispersible coating compositions are classified into colloidal dispersion type (particle size of about 0.005 to 0.05 μm) and emulsion type (particle size of about 0.05 to 0.5 μm) depending on the particle size of the resin. In this embodiment, either the colloidal dispersion type or the emulsion type may be used. For example, an acrylic resin may be used as an emulsion type coating material and a urethane resin as a colloidal dispersion type coating material, and these may be mixed to form a water-dispersible coating composition.

[0025] The first coating composition may contain a crosslinking agent in addition to the main component. When the acrylic resin or urethane resin has a crosslinking reactive group, the crosslinking agent can be blended depending on the crosslinking reactive group. Examples of crosslinking agents include, but are not limited to, methylol compounds, polyepoxy compounds, amino resins, polyaziridine compounds, polyoxazoline compounds, polyisocyanate compounds, sulfur-based compounds, hydrazine-based compounds, silane coupling agents, and chelating agents. The crosslinking agent is preferably one that dissolves in the solvent of the aqueous coating composition. Water is mainly used as the solvent for aqueous coating compositions. The amount of crosslinking agent blended is preferably, for example, 0.1 to 5 parts by mass per 100 parts by mass of the main component.

[0026] The thickness of the inner coating film is preferably 3 μm or more, more preferably 4 μm or more, and even more preferably 5 μm or more to improve impact resistance, and the upper limit of the thickness is preferably 12 μm or less, more preferably 10 μm or less to maintain improved flying performance.

[0027] The method for forming the inner coating film on the surface of the cover is not particularly limited, and any known method for applying a golf ball paint to the surface of the cover can be used, such as spray coating or electrostatic coating.

[0028] The second coating composition for forming the outer coating film contains a polyurethane coating and a solvent with a boiling point of 80°C or less. The coating film formed with this second coating composition must have an elastic recovery rate of 50% or more. The elastic recovery rate is calculated using the following formula based on the indentation work load Welast (Nm) due to the return deformation of the material and the mechanical indentation work load Wtotal (Nm). Elastic recovery rate (%) = Welast / Wtotal × 100

[0029] Elastic recovery can be measured using an Elionix ultra-microhardness tester, model ENT-2100. Elastic recovery is a parameter used in nanoindentation, a nanohardness testing method that controls the indentation load on the order of micronewtons (μN) and tracks the indenter depth with nanometer (nm) accuracy to evaluate the physical properties of a coating. Conventional methods can only measure the size of the deformation mark (plastic deformation mark) corresponding to the maximum load. However, nanoindentation automatically and continuously measures the relationship between the indentation load and the indentation depth. This eliminates the individual variability that occurs when visually measuring deformation marks with an optical microscope, allowing for highly accurate evaluation of the physical properties of the coating layer. A more desirable elastic recovery is 60% or higher. The high elasticity of the outer coating formed on the outermost surface of a golf ball contributes to its self-healing properties and excellent scratch resistance.

[0030] The following polyurethane coating material can be used as a material having such elastic recovery. Polyurethane coating materials consist of a polyol as a base agent and a polyisocyanate as a curing agent. While not limited to these, polycarbonate polyols and polyester polyols are preferred. Two types of polyester polyols, i.e., polyester polyol (A) and polyester polyol (B), may also be used. When these two types of polyester polyols are used, they have different weight-average molecular weights (Mw). It is preferable that the weight-average molecular weight (Mw) of component (A) is 20,000 to 30,000 and the weight-average molecular weight (Mw) of component (B) is 800 to 1,500. The weight-average molecular weight (Mw) of component (A) is more preferably 22,000 to 29,000, and even more preferably 23,000 to 28,000. The weight average molecular weight (Mw) of the component (B) is more preferably from 900 to 1,200, and even more preferably from 1,000 to 1,100.

[0031] Polyester polyols are obtained by polycondensation of polyols and polybasic acids, and examples of such polyols include diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, hexylene glycol, dimethylolheptane, polyethylene glycol, and polypropylene glycol, as well as triols, tetraols, and polyols having an alicyclic structure. Examples of polybasic acids include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, azelaic acid, and dimer acid; aliphatic unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, and citraconic acid; aromatic polycarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid; dicarboxylic acids having an alicyclic structure such as tetrahydrophthalic acid, hexahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and endomethylenetetrahydrophthalic acid; and tris-2-carboxyethyl isocyanurate. In particular, the polyester polyol of component (A) can be a polyester polyol having a cyclic structure introduced into the resin skeleton, such as a polyester polyol obtained by polycondensation of a polyol having an alicyclic structure such as cyclohexanedimethanol with a polybasic acid, or a polyol having an alicyclic structure with a diol or triol with a polybasic acid. On the other hand, as the polyester polyol of component (B), a polyester polyol having a multi-branched structure can be used, and examples thereof include polyester polyols having a branched structure such as "NIPPOLAN 800" manufactured by Tosoh Corporation.

[0032] Furthermore, when the above-mentioned polyester polyol is used, the weight-average molecular weight (Mw) of the entire base material is preferably 13,000 to 23,000, more preferably 15,000 to 22,000. Furthermore, the number-average molecular weight (Mn) of the entire base material is preferably 1,100 to 2,000, more preferably 1,300 to 1,850. If these average molecular weights (Mw and Mn) deviate from the above ranges, the abrasion resistance of the outer coating film may be reduced. The weight-average molecular weight (Mw) and number-average molecular weight (Mn) are measured (in terms of polystyrene) by gel permeation chromatography (hereinafter abbreviated as GPC) using a differential refractometer. When two types of polyester polyols are used, the Mw and Mn of the entire base material are within the above-mentioned ranges.

[0033] The blending amounts of the two types of polyester polyols (A) and (B) are not particularly limited, but it is preferable that the blending amount of component (A) is 20 to 30 mass % based on the total amount of the base material including the solvent, and the blending amount of component (B) is 2 to 18 mass % based on the total amount of the base material.

[0034] The polyisocyanate is not particularly limited, but may be a commonly used aromatic, aliphatic, or alicyclic polyisocyanate, such as tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, 1,4-cyclohexylene diisocyanate, naphthalene diisocyanate, trimethylhexamethylene diisocyanate, dicyclohexylmethane diisocyanate, 1-isocyanato-3,3,5-trimethyl-4-isocyanatomethylcyclohexane, etc. These may be used alone or in combination.

[0035] Examples of the modified hexamethylene diisocyanate include polyester modified hexamethylene diisocyanate and urethane modified hexamethylene diisocyanate. Examples of the derivatives of hexamethylene diisocyanate include nurate (isocyanurate), biuret, and adduct of hexamethylene diisocyanate.

[0036] In a urethane coating composition consisting primarily of polyol and polyisocyanate, the molar ratio (NCO / OH) of the hydroxyl groups (OH) of the polyol to the isocyanate groups (NCO) of the polyisocyanate is preferably 0.6 or higher, more preferably 0.65 or higher. The upper limit of this molar ratio is preferably 1.5 or lower, more preferably 1.0 or lower, and even more preferably 0.9 or lower. If the molar ratio is below the lower limit, unreacted hydroxyl groups may remain, potentially deteriorating the performance and water resistance of the outer coating film. On the other hand, if the molar ratio exceeds the upper limit, the isocyanate groups will be in excess, which will react with water to form urea groups (which are brittle), potentially reducing the performance of the outer coating film.

[0037] As the curing catalyst (organometallic compound) that promotes the reaction between polyol and polyisocyanate, an amine catalyst or an organometallic catalyst can be used. As this organometallic compound, metal soaps such as aluminum, nickel, zinc, tin, etc., which have traditionally been compounded as curing agents in two-component curing urethane paints, can be suitably used.

[0038] The solvents used for the polyol base and the polyisocyanate curing agent each have a boiling point of 80°C or less. This allows for a coating of approximately uniform thickness to be formed on the golf ball surface, including the edges of the dimples, even when a thick coating is to be formed. Examples of solvents with a boiling point of 80°C or less include hydrocarbon solvents such as normal hexane (68°C), cyclohexane (80°C), and benzene (80°C); ester solvents such as methyl acetate (57°C) and ethyl acetate (77°C); and ketone solvents such as acetone (56°C) and methyl ethyl ketone (79°C) (boiling points are in parentheses). Considering the impact on the human body and the environment, ester solvents such as ethyl acetate and ketone solvents such as methyl ethyl ketone (MEK) are more preferred.

[0039] Two or more of these solvents may be mixed and used, or these solvents may be mixed with a solvent having a boiling point above 80°C. The amount of solvent having a boiling point of 80°C or less is preferably 20% by mass or more, more preferably 40% by mass or more, based on the total mass of the coating composition. The total mass of the coating composition is the sum of the total mass of the base agent including the solvent and the total mass of the curing agent including the solvent.

[0040] From the viewpoint of scratch resistance and peel resistance, the thickness of the outer coating film at the dimple edge is preferably 10 μm or more, and more preferably 12 μm or more. The thicker the outer coating film, the better the scratch resistance and peel resistance. However, if it is too thick, it may affect the aerodynamic characteristics of the golf ball. Therefore, the upper limit of the thickness of the outer coating film at the dimple edge is preferably 25 μm or less, and more preferably 20 μm or less.

[0041] The edge ratio, which is the ratio of the film thickness at the edge of a dimple to the film thickness at the center of the dimple, indicates a more uniform film thickness at the dimple as the ratio approaches 100%, and serves as an index for evaluating the uniformity of a coating film. An edge ratio of 50% or more is preferred, with 70% or more being more preferred. Typically, when attempting to form a thick coating on the recessed surface of a dimple, the film thickness at the shallow edge of the recess will be thin, while the film thickness at the deep center of the recess will be thick. This tendency becomes more pronounced when forming a coating with a high elastic recovery rate, making it difficult to form a coating thickness of 10 μm or more at the edge of a dimple. In this embodiment, by using a solvent with a boiling point of 80°C or less, an edge ratio of 50% or more can be achieved even when forming an outer coating with an elastic recovery rate of 50% or more at a thickness of 10 μm or more on the edge of a dimple.

[0042] Furthermore, the second coating composition that forms the outer coating film may further contain known coating ingredients, such as thickeners, ultraviolet absorbers, fluorescent whitening agents, pigments, etc., in appropriate amounts, as needed.

[0043] The method for forming the outer coating film is not particularly limited, and any known method for applying a golf ball paint to the cover surface, such as spray coating or electrostatic coating, can be used. In this way, the outer coating film can be formed on the surface of the inner coating film.

[0044] For both the inner and outer coating films, a step of drying the coating film may be carried out after the coating film is formed. The drying conditions may be the same as known conditions for drying urethane paints, and in this embodiment, for example, the drying temperature may be about 40°C or higher, particularly 40 to 60°C, and the drying time may be 20 to 90 minutes, particularly 40 to 50 minutes.

[0045] The golf ball of this embodiment can be obtained by the golf ball manufacturing method described above. The golf ball of this embodiment includes a core, a cover having a plurality of dimples, and a coating film located on the surface of the cover, the coating film having a laminated structure including at least a first coating film (inner coating film) on the inside of the golf ball and a second coating film (outer coating film) on the outside of the golf ball. The outer coating film contains polyurethane paint, and since the characteristics of the coating film, such as an elastic recovery rate of 50% or more and an edge ratio of the outer coating film of 50% or more, have already been described, the core and cover will be described below.

[0046] The core can be formed primarily from a base rubber. A wide variety of rubbers (thermosetting elastomers) can be used as the base rubber, including, but not limited to, polybutadiene rubber (BR), styrene butadiene rubber (SBR), natural rubber (NR), polyisoprene rubber (IR), polyurethane rubber (PU), butyl rubber (IIR), vinyl polybutadiene rubber (VBR), ethylene propylene rubber (EPDM), nitrile rubber (NBR), and silicone rubber. Examples of polybutadiene rubber (BR) that can be used include 1,2-polybutadiene and cis-1,4-polybutadiene.

[0047] In addition to the base rubber as the main component, the core may optionally contain, for example, a co-crosslinking agent, a crosslinking agent, a filler, an antioxidant, an isomerizing agent, a mastication accelerator, sulfur, and an organic sulfur compound. Alternatively, a thermoplastic elastomer, an ionomer resin, or a mixture thereof may be used as the main component instead of the base rubber.

[0048] The core has a substantially spherical shape. The upper limit of the outer diameter of the core is preferably about 42 mm or less, more preferably about 41 mm or less, and even more preferably about 40 mm or less. The lower limit of the outer diameter of the core is preferably about 5 mm or more, more preferably about 15 mm or more, and most preferably about 25 mm or more. The core may be solid or hollow. The core may be a single layer or may be a core consisting of multiple layers, such as a center core and a surrounding layer.

[0049] The core can be molded using any known method for molding golf ball cores. For example, but not limited to, a core can be obtained by kneading materials containing a base rubber in a kneading machine and then pressure-vulcanizing and molding the mixture in a round mold. Furthermore, a core having multiple layers can be molded using any known method for molding multilayer solid cores. For example, a center core can be obtained by kneading materials in a kneading machine and pressure-vulcanizing and molding the mixture in a round mold. Then, a surrounding layer can be obtained by kneading materials in a kneading machine and molding the mixture into a sheet. The center core is then covered with the sheet and pressure-vulcanized and molded in a round mold. This results in a multilayer core.

[0050] The cover can be formed using, but is not limited to, thermoplastic polyurethane, ionomer resin, or a mixture thereof, and it is particularly preferable to use ionomer resin because of its affinity with the inner coating.

[0051] The thermoplastic polyurethane material has a structure consisting of a soft segment made of a polymeric polyol (polymeric glycol) and a hard segment made of a chain extender and polyisocyanate. The polymeric polyol used as the raw material is not particularly limited, but in the present invention, polyester polyols and polyether polyols are preferred. Specific examples of polyester polyols include adipate polyols such as polyethylene adipate glycol, polypropylene adipate glycol, polybutadiene adipate glycol, and polyhexamethylene adipate glycol, and lactone polyols such as polycaprolactone polyol. Examples of polyether polyols include poly(ethylene glycol), poly(propylene glycol), and poly(tetramethylene glycol).

[0052] The chain extender is not particularly limited, but in the present invention, a low molecular weight compound having two or more active hydrogen atoms in the molecule that can react with an isocyanate group and a molecular weight of 2,000 or less can be used, and among these, aliphatic diols having 2 to 12 carbon atoms are preferred. Specific examples include 1,4-butylene glycol, 1,2-ethylene glycol, 1,3-butanediol, 1,6-hexanediol, and 2,2-dimethyl-1,3-propanediol, and among these, 1,4-butylene glycol is particularly preferred.

[0053] The polyisocyanate compound is not particularly limited, but in the present invention, for example, one or more compounds selected from the group consisting of 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, naphthylene 1,5-diisocyanate, tetramethylxylene diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, trimethylhexamethylene diisocyanate, and dimer acid diisocyanate can be used. However, depending on the type of isocyanate, it may be difficult to control the crosslinking reaction during injection molding. Therefore, in the present invention, from the viewpoint of the balance between stability during production and the physical properties that are expressed, the aromatic diisocyanate 4,4'-diphenylmethane diisocyanate is preferred.

[0054] The ionomer resin may be, but is not limited to, one having the following component (a) and / or component (b) as the base resin. Optionally, the following component (c) can be added to this base resin. Component (a) is an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester ternary random copolymer and / or a metal salt thereof; component (b) is an olefin-unsaturated carboxylic acid binary random copolymer and / or a metal salt thereof; and component (c) is a thermoplastic block copolymer having a polyolefin crystalline block and a polyethylene / butylene random copolymer.

[0055] In addition to the thermoplastic polyurethane or ionomer resin as the main component, the resin for the cover can also contain a thermoplastic resin or elastomer other than thermoplastic polyurethane. Specifically, one or more of the following can be used: polyester elastomer, polyamide elastomer, ionomer resin, styrene block elastomer, hydrogenated styrene butadiene rubber, styrene-ethylene-butylene-ethylene block copolymer or modified product thereof, ethylene-ethylene-butylene-ethylene block copolymer or modified product thereof, styrene-ethylene-butylene-styrene block copolymer or modified product thereof, ABS resin, polyacetal, polyethylene, and nylon resin. Polyester elastomer, polyamide elastomer, and polyacetal are particularly preferred because they maintain good productivity while improving resilience and abrasion resistance through reaction with isocyanate groups. When the above components are blended, their blend amounts are appropriately selected depending on the desired adjustment of the cover material hardness, improvement of resilience, improvement of fluidity, improvement of adhesion, etc., and are not particularly limited, but are preferably 5 parts by mass or more per 100 parts by mass of the thermoplastic polyurethane component. There is also no particular upper limit on the blend amount, but they are preferably 100 parts by mass or less, more preferably 75 parts by mass or less, and even more preferably 50 parts by mass or less per 100 parts by mass of the thermoplastic polyurethane component. Other components that may be added include polyisocyanate compounds, fatty acids or derivatives thereof, basic inorganic metal compounds, fillers, etc.

[0056] The cover can be formed by any known molding method for golf ball covers. For example, without particular limitation, the cover can be formed so as to cover the core by placing the core in a mold and injection-molding a resin composition for the cover. The mold for molding the cover has multiple protrusions for forming dimples on the surface of the cover. The size, shape, number, etc. of the dimples formed on the surface of the cover can be designed appropriately depending on the desired aerodynamic characteristics of the golf ball.

[0057] The thickness of the cover is not limited to, but the lower limit is preferably 0.2 mm or more, more preferably 0.4 mm or more, and the upper limit is preferably 4 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less.

[0058] The cover material hardness is not limited to, but the upper limit is preferably about 60 or less, more preferably about 55 or less, and even more preferably about 50 or less, in Shore D. The lower limit is preferably about 35 or more, more preferably about 40 or more, in Shore D. The cover material hardness is measured by molding the resin material of the cover into a 2 mm thick sheet, allowing it to stand for at least two weeks, and then measuring the Shore D hardness in accordance with ASTM D2240-95. [Example]

[0059] Examples and comparative examples of the present invention will be described below.

[0060] When producing the golf balls of the Examples and Comparative Examples, the paint films of the golf balls were produced using the paint formulations shown in Table 1. The formulations in Table 1 are expressed in parts by mass. The paint film thickness of the produced golf balls was measured, and a sand abrasion test and a sand-water abrasion test were conducted to evaluate peel resistance and scratch resistance.

[0061] In the paint formulation for the inner coating shown in Table 1, an emulsion-based thermoplastic acrylic resin (trade name: NeoCryl A-6092, manufactured by DSM Coating Resins) was used as the acrylic resin, which was one of the main components. An aqueous urethane dispersion (trade name: NeoRez R-967, manufactured by DSM Coating Resins) was used as the urethane resin, which was one of the main components. In addition to the main component, a crosslinking agent was also blended into the inner coating. The crosslinking agent used was an aziridine-based crosslinking agent (NeoCryl CX-100, manufactured by DSM Coating Resins). A paint containing a 100:1.3:3 ratio of main component:crosslinking agent:water was spray-painted onto the cover surface on which dimples had been formed, forming an inner coating. In Comparative Example 3, no inner coating was formed, and the cover surface was subjected to plasma treatment. In other words, in Comparative Example 3, the coating consisted of only a single layer: the outer coating.

[0062] In the coating formulation for the outer coating shown in Table 1, a polyester polyol with a weight-average molecular weight (Mw) of 28,000 was used as the main polyol (solids). This was synthesized by the following method. A reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, and a thermometer was charged with 140 parts by mass of trimethylolpropane, 95 parts by mass of ethylene glycol, 157 parts by mass of adipic acid, and 58 parts by mass of 1,4-cyclohexanedimethanol, and the mixture was heated to 200-240°C with stirring and heated (reacted) for 5 hours. This resulted in a polyester polyol with an acid value of 4, a hydroxyl value of 170, and a weight-average molecular weight (Mw) of 28,000.

[0063] As the isocyanate (solid content) of the curing agent, hexamethylene diisocyanate (HDI) was used in the form of a nurate (isocyanurate) of hexamethylene diisocyanate (HMDI) available from Asahi Kasei Corporation under the trade name Duranate TPA-100 (NCO content 23.1%, non-volatile content 100%).

[0064] Ethyl acetate (boiling point: 77°C) and butyl acetate (boiling point: 126°C) were used as solvents for the base agent and curing agent of the outer coating. The base agent and curing agent were mixed and the resulting paint was sprayed onto the inner coating to form the outer coating. The elastic recovery of the outer coating in Table 1 was measured using the following method.

[0065] [Method for measuring elastic recovery rate] A coating sheet with a thickness of 50 μm was formed for each formulation, and measurements were made using this coating sheet. The measuring device used was an ultra-micro hardness tester "ENT-2100" manufactured by Elionix, and the measurement conditions were as follows: Indenter: Berkovich indenter (material: diamond, angle α: 65.03°) Load F: 0.2mN Loading time: 10 seconds ·Holding time: 1 second ·Unloading time: 10 seconds The elastic recovery rate was calculated using the following formula based on the indentation work load Welast (Nm) due to the return deformation of the coating film and the mechanical indentation work load Wtotal (Nm). Elastic recovery rate (%) = Welast / Wtotal × 100

[0066] The cover of each golf ball was formulated with 50 parts by weight of Himilan 1605 (trade name), an ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals, and 50 parts by weight of AM7329 (trade name), both manufactured by Mitsui Dow Polychemicals. The cover material hardness was 63 Shore D.

[0067] The intermediate layer of each golf ball was formulated with 35 parts by weight of Himilan 1706 (an ionomer resin of ethylene-methacrylic acid copolymer manufactured by Mitsui Dow Polychemicals), 15 parts by weight of Himilan 1557 (also manufactured by Mitsui Dow Polychemicals), 50 parts by weight of Himilan 1605 (also manufactured by Mitsui Dow Polychemicals), and 1.1 parts by weight of trimethylolpropane.

[0068] The core of each golf ball was formulated as follows: 20 parts by weight of polybutadiene (product name BR51, manufactured by JSR Corporation) as a base rubber; 80 parts by weight of polybutadiene (product name BR-01, manufactured by JSR Corporation); 28.5 parts by weight of zinc acrylate (manufactured by Wako Pure Chemical Industries, Ltd.); 1.0 part by weight of dicumyl peroxide (product name Percumyl D, manufactured by NOF Corporation) as an organic peroxide; 0.1 part by weight of 2,2-methylenebis(4-methyl-6-butylphenol) (product name Nocrac NS-6, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) as an antioxidant; 33.0 parts by weight of barium sulfate (product name Precipitated Barium Sulfate #100, manufactured by Sakai Chemical Industry Co., Ltd.); 4.0 parts by weight of zinc oxide (product name Three-type Zinc Oxide, manufactured by Sakai Chemical Industry Co., Ltd.); and 0.5 part by weight of pentachlorothiophenol zinc salt (manufactured by Wako Pure Chemical Industries, Ltd.) as an organic sulfur compound.

[0069] [Method for measuring film thickness] The film thicknesses of the inner and outer coating films at the center and edge of the dimples in Table 1 were calculated using the following measurement method. First, lines 1 to 5 were drawn vertically at equal intervals on the cross section of the dimple 12 of the cover 10 shown in Figure 1, and these lines were designated No. 1, No. 2, No. 3, No. 4, and No. 5, respectively, from the edge E of the dimple to the opposite edge E'. The film thicknesses of the inner coating film 22 and the outer coating film 20 were measured along each line. The film thicknesses were measured by cutting the golf ball and measuring the film thickness of the cross section at each position using a microscope. Then, for the inner and outer coating films, the average film thicknesses at No. 1 and No. 5 were taken as the film thickness at the edge of the dimple, and the average film thicknesses at No. 2, No. 3, and No. 4 were taken as the film thickness at the center of the dimple.

[0070] Then, the edge ratio, which is the ratio of the film thickness at the edge portion to the film thickness at the center portion of the dimple, was calculated using the following formula. Edge ratio [%] = (thickness of edge part) / (thickness of center part) × 100

[0071] [Sand abrasion test] The sand abrasion test in Table 1 was conducted as follows. Approximately 4 kg of sand with a size of approximately 5 mm was placed in a pot mill with an outer diameter of 210 mm, and 15 golf balls were placed in the pot mill. The sand was then stirred in the pot mill at a rotation speed of 50 to 60 rpm for 120 minutes. The golf balls were then removed from the pot mill, and the appearance of the golf ball surface was observed and evaluated for peel resistance and scratch resistance according to the following criteria.

[0072] Peel resistance was evaluated by irradiating the golf balls with UV light and observing the degree of peeling due to wear on the surface of each golf ball. Scoring was performed based on a criterion: no peeling was scored as 5 points, slight peeling was scored as 3 points, and noticeable large peeling was scored as 1 point. The average of the evaluation results for five golf balls was taken as the peel resistance. A score of 2 or less was evaluated as ×, more than 2 to 2.5 points as △, more than 2.5 to 4 points as ◯, and more than 4 points as ◎.

[0073] The scratch resistance was evaluated by magnifying the surface of the golf ball with a magnifying glass and observing the degree of fine scratches on the coating. Evaluation was based on a scale of 5 points for no noticeable scratches, 3 points for small scratches, and 1 point for large scratches or noticeable loss of gloss. The average of the evaluation results for five golf balls was taken as the scratch resistance. A score of 2 or less was evaluated as ×, more than 2 to 2.5 points as △, more than 2.5 to 4 points as ◯, and more than 4 points as ◎.

[0074] [Sand and water abrasion test] The sand-water abrasion test in Table 1 was conducted as follows. Approximately 4 kg of sand with a size of approximately 5 mm and water were placed in a pot mill with an outer diameter of 210 mm, and 15 golf balls were placed in the pot mill. The mixture was then stirred in the pot mill at a rotation speed of 50 to 60 rpm for 120 minutes. The golf balls were then removed from the pot mill, irradiated with UV light, and the degree of peeling due to abrasion on the surface of each golf ball was observed. Evaluation was based on a rating scale of 5 points for no peeling, 3 points for small peeling, and 1 point for noticeable large peeling. The average of the evaluation results for the five golf balls was taken as the peel resistance. A score of 2 or less was evaluated as ×, more than 2 to 2.5 points as △, more than 2.5 to 4 points as ◯, and more than 4 points as ◎.

[0075] [Table 1]

[0076] As shown in Table 1, in Examples 1 to 4, a solvent with a boiling point of 80°C or less was used in the formulation of the outer coating, and therefore an outer coating film with a thickness of 10 mm or more could be formed on the edge portions of the dimples at a high edge ratio of 70% or more. Furthermore, because an outer coating film with an elastic recovery rate of 60% could be formed at such a thickness, it exhibited excellent scratch resistance and excellent peel resistance in both sand abrasion tests and sand-water abrasion tests. In particular, in Example 4, a remarkably thick outer coating film of 15 mm could be formed on the edge portions of the dimples at a high edge ratio of 80% or more, and it also exhibited remarkably excellent scratch resistance and peel resistance.

[0077] In Example 5, a solvent with a boiling point of 80°C or less and a solvent with a boiling point above 80°C were used in combination to form the outer coating, but because the blending ratio of the solvent with a boiling point of 80°C or less was 20% or more, an outer coating film with a thickness of 8 mm could be formed on the edge of the dimples with an edge ratio of 57%. Therefore, good results were obtained in terms of both scratch resistance and peel resistance.

[0078] On the other hand, in Comparative Example 1, the boiling point of the solvent used in formulating the outer coating was over 80°C, resulting in a low edge ratio of 43% and a thin outer coating thickness of 6 mm at the edges of the dimples. As a result, despite the high elastic recovery of 60%, scratch resistance was significantly poor, and peel resistance in the sandy water abrasion test was also poor.

[0079] In addition, in Comparative Example 2, the boiling point of the solvent used to formulate the outer coating was below 80°C, so a 9 mm thick outer coating could be formed on the edge of the dimple with a high edge ratio of 64%, and excellent peel resistance was obtained in both the sand abrasion test and the sand-water abrasion test.However, due to the paint formulation of the outer coating, the elastic recovery rate of the outer coating was low at 20%, resulting in significantly inferior scratch resistance.

[0080] Furthermore, in Comparative Example 3, the boiling point of the solvent used in formulating the outer coating was below 80°C, so a 10 mm thick outer coating could be formed on the edge of the dimples with a high edge ratio of approximately 70%. However, because no inner coating was formed on the cover surface and only a single layer of outer coating was used, the scratch resistance was poor despite the high elastic recovery rate of 60%, and the peel resistance in the sand abrasion test and sand-water abrasion test did not show the same improvement as in Examples 1 to 4. [Explanation of symbols]

[0081] 10 Cover 12 dimples 20 Outer coating 22 Inner coating film

Claims

1. forming a first coating on a surface of a cover having a plurality of dimples; forming a second coating on the surface of the first coating; 1. A method for manufacturing a golf ball, comprising: The first coating film is formed by a first coating composition containing an acrylic resin and a urethane resin, and a ratio of the acrylic resin to a total mass of the acrylic resin and the urethane resin is 50 mass% or more; The second coating film is formed by a second coating composition containing a polyurethane coating and a solvent having a boiling point of 80° C. or less, A method for producing a golf ball, wherein the second coating has an elastic recovery rate of 50% or more.

2. 2. The method for manufacturing a golf ball according to claim 1, wherein the thickness of the second coating film at the edge portion of the dimple is 10 [mu]m or more.

3. 3. The method for manufacturing a golf ball according to claim 1, wherein the second coating is formed by spray coating.

4. 4. The method for manufacturing a golf ball according to claim 1, wherein the amount of the solvent having a boiling point of 80° C. or less based on the total amount of the second coating composition is 20% by mass or more.

5. A golf ball comprising a core, a cover having a plurality of dimples, and a coating film disposed on a surface of the cover, the coating film having a layered structure including at least a first coating film on an inner side of the golf ball and a second coating film on an outer side of the golf ball, the first coating film contains an acrylic resin and a urethane resin, and a ratio of the acrylic resin to a total mass of the acrylic resin and the urethane resin is 50 mass% or more; A golf ball in which the second coating film contains polyurethane paint, the second coating film has an elastic recovery rate of 50% or more, and an edge ratio, which is the ratio of the film thickness of the second coating film at the edge portion of the dimple to the film thickness of the second coating film at the center portion of the dimple, is 50% or more.

6. 6. The golf ball according to claim 5, wherein the thickness of the second coating at the edge portion of the dimple is 10 [mu]m or more. End

Citation Information

Patent Citations

  • Golf ball

    JP2006051357A

  • Golf ball

    JP2009100894A

  • Coating composition for golf ball

    JP2017077357A

  • Golf ball

    JP2017109005A

  • Golf ball

    JP2019080840A